Metformin as an archetype immuno-metabolic adjuvant for cancer immunotherapy. (3rd October 2019) - Verdura, Sara; Cuyàs, Elisabet; Martin-Castillo, Begoña; Menendez, Javier A.
ABSTRACT: The development of a single immuno-metabolic adjuvant capable of modulating, in the appropriate direction and intensity, the complex antagonistic and symbiotic interplays between tumor cells, immune cells, and the gut microbiota may appear pharmacologically implausible. Metformin might help solve this conundrum and beneficially impact the state of cancer-immune system interactions.